Arctic Edible Brown Alga Fucus distichus L.: Biochemical Composition, Antiradical Potential and Human Health Risk - Ekaterina D. Obluchinskaya; Olga N. Pozharitskaya; Elena V. Gorshenina; Denis V. Zakharov; Elena V. Flisyuk; Inna I. Terninko; Yuliya E. Generalova; Alexander N. Shikov (Plants, 2023)
Fucus distichus L. is the dominant canopy-forming macroalga in the rocky intertidal areas of the Arctic and Subarctic. In the present study, the impact of the geographic location of F. distichus collected in the Baffin Sea (BfS), Norwegian Sea (NS), White Sea (WS), and Barents Sea (BS) on the variations in biochemical composition, antiradical properties, and health risk was evaluated. The accumulation of main carbohydrates (fucoidan, mannitol, and alginic acid) varied from 335 mg/g dry weight (DW) in NS to 445 mg/g DW in BS. The highest level of the sum of polyphenols and flavonoids was found in samples of F. distichus from WS and was located in the following ranking order: BS < BfS < NS < WS. The 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity of seaweed is correlated with its phenolic content. It is notable that in most Arctic F. distichus samples, Cd, Cr, Pb, and Ni were not detected or their concentrations were below the limit of quantification. According to calculated targeted hazard quotient and hazard index values, all studied samples of Arctic F. distichus are safe for daily consumption as they do not pose a carcinogenic risk to the health of adults or children. The results of this study support the rationale for using Arctic F. distichus as a rich source of polysaccharides, polyphenols, and flavonoids with important antiradical activity. We believe that our data will help to effectively use the potential of F. distichus and expand the use of this algae as a promising and safe raw material for the food and pharmaceutical industries.